Peran Teknologi Informasi dalam Implementasi Kurikulum PAI di SMA Negeri 1 Sangatta Utara - Muhammad Nabil Priambada; Aprianti Astuti; Anjani Putri Belawati Pandiangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research discusses the role of information technology in implementing the Islamic Education curriculum at SMA Negeri 1 Sangata Utara. In researchusing qualitative methods,this method uses the results of uinterviews and direct observation questions and answers with informants,principals and PAI teachers to find out the role of information technology in implementing the PAI curriculum at SMA Negeri 1 Sangata Utara secondly,what are the information technologies in implementing the curriculum is a student learning design in information technology learning,the use of learning resources such as educational videos,interactive simulations and other online resources to enrich the learning experience with a deep understanding of Islamic concepts. Information technology in implementation at SMAN 1 Sangata Utara has applied learning using technology, for example the technology used is the use of PowerPoint and the use of the Canva application. The role of information technology in implementing the Pai program includes information technology as a tool to support the implementation of Islamic religious education.